Bullous pemphigoid induced by dipeptidyl peptidase-4 (DPP-4) inhibitors: a pharmacovigilance-pharmacodynamic/pharmacokinetic assessment through an analysis of the vigibase®. Issue 11 (2nd November 2019) - Carnovale, Carla; Mazhar, Faizan; Arzenton, Elena; Moretti, Ugo; Pozzi, Marco; Mosini, Giulia; Leoni, Olivia; Scatigna, Marco; Clementi, Emilio; Radice, Sonia
ABSTRACT: Objectives : To examine the signals of bullous pemphigoid (BP) with dipeptidyl peptidase-4 inhibitors (DPP-4i) in VigiBase® and the potential role of their pharmacodynamic/pharmacokinetic parameters in the occurrence of BP. Methods : Case/non-case analyses were performed in VigiBase® to examine the signal of BP [reporting odds ratio (ROR)] for gliptins. Secondly, the authors performed linear regression analyses to explore the association between DPP-4i signals for BP and their affinities toward different target enzymes (DPP-2, DPP-4, DPP-8, and DPP-9) and their volume of distribution (Vd). Results : A significant BP signal was found for DPP-4i. The ROR for pooled DPP-4i was 179.48 (95% CI: 166.41–193.58). The highest ROR was found for teneligliptin 975.04 (801.70–1185.87) and lowest for saxagliptin 18.9 (11.5–30.9). Linear regression analyses showed a considerable trend to significance for the linear correlation between the BP signal and gliptin affinity at DPP-4 (slope = 1.316 [−0.4385–3.21], p = 0.067, R 2 = 0.40) but not the other enzyme targets, nor for Vd. Conclusion : The findings suggest a clinical relevance of gliptins selectivity for DDP-4 in the development of BP as a result of exposure to these drugs. Future preclinical and clinical studies are needed for a better understanding of this correlation.